DIABETIC RETINAL NEURODEGENERATION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Diabetic retinopathy (DR) is widely recognized as one of the leading causes of blindness and low vision among people of working age. Its high prevalence among patients with diabetes mellitus (DM) makes this disease a key problem in ophthalmology. Diagnosis and grading of DR are traditionally based on the detection of vascular changes in the retina: microaneurysms, hemorrhages, avascular zones and neovascularization. These signs serve as important markers for assessing the severity of the disease and choosing treatment tactics. However, in recent decades, research has significantly expanded our understanding of the pathogenesis of DR. Compelling evidence has accumulated indicating that retinal neurodegeneration may precede vascular changes. This early neuronal damage includes dysfunction and death of retinal ganglion cells, changes in photoreceptors, and activation of microglia, indicating the complex nature of the disease. Oxidative stress, inflammation, and impaired glucose metabolism are key triggers for these changes. The early onset of neurodegeneration suggests that damage to neural tissue may play an equally important role in the progression of DR as vascular disorders. Moreover, neurodegeneration is considered as an independent therapeutic target, which opens up new prospects for the development of treatment methods. Neuroprotective approaches aimed at preserving neuronal function are already attracting the attention of researchers, and their inclusion in therapeutic strategies may significantly improve treatment outcomes.